2019
DOI: 10.1016/j.jtho.2018.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Drug Conjugates for the Therapy of Thoracic Malignancies

Abstract: Antibody-drug conjugates (ADCs) are a novel class of therapeutic agents incorporating both target-specific monoclonal antibodies and cytotoxic small molecules via a chemical linker. They were first introduced into the clinic for the treatment of advanced hematologic malignancies. The only approved ADC for solid tumors targets erb-b2 receptor tyrosine kinase (HER2), a validated antigen in breast cancer. Many ADCs are under active investigation for various types of solid tumors. In this article, we review the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 101 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…The payloads used in ADCs are selected small molecules with high potency and proper hydropholicity [20,21]. Another important parameter is drug-antibody ratio (DAR), which is defined as the average number of payload molecules attached to a single mAb.…”
Section: Characteristics Of Payloadsmentioning
confidence: 99%
“…The payloads used in ADCs are selected small molecules with high potency and proper hydropholicity [20,21]. Another important parameter is drug-antibody ratio (DAR), which is defined as the average number of payload molecules attached to a single mAb.…”
Section: Characteristics Of Payloadsmentioning
confidence: 99%
“…51,145 A confirmation phase 3 EV-301 trial exploring EVs compared with chemotherapy is ongoing. 4.2.2 | Newly diagnosed advanced cancer First-line application of TDM-1 was evaluated for advanced HER2-positive breast cancer patients, wherein the phase 3 MARIANNE trial compared T-DM1 plus pertuzumab and T-DM1 monotherapy with trastuzumab plus taxane (control group). Results showed that T-DM1 with or without pertuzumab had similar efficacy with the control group (median PFS: 15.2 months vs. 14.1 months vs. 13.7 months; response rate: 64.2% vs. 59.7% vs. 67.9%; median response duration: 21.2 months vs. 20.7 months vs. 12.5 months), while there was a lower rate of AEs over grade 3 (46.2% vs. 45.4% vs. 54.1%).…”
Section: Previously Treated Advanced Cancermentioning
confidence: 99%
“…13,174 The conjugation strategy affects the homogeneity of the drug-to-antibody ratio (DAR, the average number of cytotoxic molecules attached to each antibody), the release time of cytotoxic payloads, and off-target toxicity. 4 Compared with traditional nonspecific conjugation, site-specific conjugations could increase the homogeneity, stability, pharmacokinetics, and decrease toxicity. [175][176][177] However, considering the inefficient chemistry and immunogenicity, new technologies are still under development for a better controlled DAR and homogeneity of ADC.…”
Section: Optimization Of Adc Structurementioning
confidence: 99%
See 2 more Smart Citations